Lifetime ostracism experiences and mechanisms of pain - Walsh, Kaitlyn T.; Boring, Brandon L.; Nanavaty, Namrata; Carter-Sowell, Adrienne R.; Mathur, Vani A. (Frontiers in Pain Research, 2022)
One social mechanism by which marginalization is enacted is via ostracism. Recent research has demonstrated ostracism’s impact on physical health, but little is known about the relationship between accumulated lifetime experiences of ostracism and pain. Despite recent calls for added attention to social modulation of pain and social indicators of pain disparities, the impact of specific social factors on pain – including those of ostracism – are not well understood. Results of laboratory studies on the effects of acute ostracism experiences on pain sensitivity have been mixed. However, these studies have not considered lived and repeated experiences of ostracism, and primarily included single static measures of pain sensitivity. Additionally, inclusion and representation of the relationship between ostracism experiences and pain among people with minoritized identities are lacking in the current literature. In this study, we explored accumulated lifetime experiences of ostracism as a potential contributing factor to enhanced pain and one social mechanism by which societal inequity may create and maintain inequity in pain. We extracted measures of lifetime experiences of ostracism from six studies focused on social factors and (non-chronic) pain conducted between 2016-2020 (n = 505 adults). To retain and examine diversity within the sample, we used moderation and within-group analyses. Results indicate that greater experiences of lifetime ostracism are associated with lower cold pain tolerance, but not other pain measures, in the whole sample. Moderation and within-group analyses reveal opposing patterns of results between populations included in the extant literature (White participants, convenience samples) and those under-represented in the scientific literature (racialized groups, community samples). This study provides an example of a diversity science approach to examining social indicators of pain, illustrates the limited generalizability of previous studies on ostracism and pain, and highlights the need for increased representation and inclusion to understand mechanisms of pain and inequity.